Numerical Analysis of Heat Transfer and Flow Characteristics in A Semi Cylindrical Solar Air Heater (International Journal of Scientific Trends, 2026)
In this article, a numerical investigation will be conducted on the properties of heat transfer and flow in a semi-cylindrical solar air heater through COMSOL Multiphysics. A three-dimensional model was created to investigate the relationship between heat performance, air flow and solar energy absorption. The convective heat transfer coefficient, useful energy gain, and air temperature were some of the key performance parameters that were developed and executed using user-defined variables in COMSOL. In order to simulate realistic operating conditions, the simulation was performed at the inlet velocity of 0.01 m/s, with the variation of solar radiation within the time periods of 08:00 to 17:00. It was also in the model that the natural convection heat loss on the outer surface of the collector was taken into account. The findings indicate that the semi-cylindrical design is more effective in heat transfer and increase in air temperature hence, increased energy usage efficiency than the conventional design. The established model is an effective computational aid in making predictions on performance and the design optimization of solar air heaters.